The role of myeloid derived suppressor cells in musculoskeletal disorders - Ren, Yi; Bäcker, Henrik; Müller, Michael; Kienzle, Arne (Frontiers in Immunology, 2023)
The immune system is closely linked to bone homeostasis and plays a pivotal role in several pathological and inflammatory conditions. Through various pathways it modulates various bone cells and subsequently sustains the physiological bone metabolism. Myeloid-derived suppressor cells (MDSCs) are a group of heterogeneous immature myeloid-derived cells that can exert an immunosuppressive function through a direct cell-to-cell contact, secretion of anti-inflammatory cytokines or specific exosomes. These cells mediate the innate immune response to chronic stress on the skeletal system. In chronic inflammation, MDSCs act as an inner offset to rebalance overactivation of the immune system. Moreover, they have been found to be involved in processes responsible for bone remodeling in different musculoskeletal disorders, autoimmune diseases, infection, and cancer. These cells can not only cause bone erosion by differentiating into osteoclasts, but also alleviate the immune reaction, subsequently leading to long-lastingly impacted bone remodeling. In this review, we discuss the impact of MDSCs on the bone metabolism under several pathological conditions, the involved modulatory pathways as well as potential therapeutic targets in MDSCs to improve bone health.